2013
DOI: 10.1097/mib.0b013e31828075e7
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of 71 European Crohnʼs Disease Susceptibility Loci in a Japanese Population

Abstract: Our study suggests that there is a differential genetic background of CD susceptibility between Japanese and European populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 37 publications
2
39
1
Order By: Relevance
“…In contrast, we found that LRRK2 M2397T, a susceptibility allele for European ancestry but not for Japanese or Korean CD (3,23,25,33,54), was associated with Paneth cell defect in Japanese, but not North American CD. There are several important considerations when interpreting these findings.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…In contrast, we found that LRRK2 M2397T, a susceptibility allele for European ancestry but not for Japanese or Korean CD (3,23,25,33,54), was associated with Paneth cell defect in Japanese, but not North American CD. There are several important considerations when interpreting these findings.…”
Section: Discussioncontrasting
confidence: 51%
“…In particular, the NOD2 variants associated with European ancestry CD are not polymorphic in Japanese populations (24). In addition, while ATG16L1 T300A is polymorphic in Japanese cohorts, it has not been associated with CD susceptibility (25). In contrast, SNPs that are more frequently associated with CD in Asian populations include those that tag TNFSF15, IL23R, ATG16L2, STAT3, GPR35, MHC Class II, and ZNF365, among others (5,(21)(22)(23)25).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 97%
See 1 more Smart Citation
“…3 Genome-wide association studies have identified 163 susceptibility loci associated with inflammatory bowel disease (IBD), 140 of which are associated with CD. 2 A non-synonymous single nucleotide polymorphism (SNP) in the gene encoding the autophagy-related 16-like protein (ATG16L1) has been associated with increased risk for developing CD in multiple populations [4][5][6][7] and specifically with the development of ileal CD. 8 The ATG16L1 CD-associated gene variant is common in the population with 33.2% of people from Western European descent being homozygous for the risk variant.…”
Section: Introductionmentioning
confidence: 99%
“…99 Specifically with regards to the TL1A-DR3 pathway in IBD, a TNFSF15 haplotype is associated with higher TL1A expression, increased risk of CD, intestinal fibrostenosis, and greater need for surgery. [100][101][102] In mice, constitutive TL1A overexpression causes spontaneous ileitis with increased collagen deposition. 103,104 Under colitogenic conditions induced by chronic dextran sulfate sodium (DSS) treatment or adoptive T-cell transfer, increased inflammation, fibrosis, and fibrostenotic lesions in the gut are seen.…”
Section: Tl1amentioning
confidence: 99%